Mobile Money and Investment by Women Businesses in Sub-Saharan Africa - Islam, Asif; Muzi, Silvia (World Bank, Washington, DC, 2020)
This study connects two important findings in Sub-Saharan Africa. First, digital technologies such as mobile money have become widespread and have increased investment by businesses, especially in East Africa. Second, women-owned business in the region significantly lag their male counterparts in capital investments. Using data for 16 Sub-Saharan African economies, the study connects the two findings by exploring whether mobile money use by women-owned firms increases their investment. The findings indicate that the positive relationship between mobile money use and investment is largely driven by women-owned firms and is statistically insignificant for men-owned firms. Potential channels of these effects are explored. Women-owned firms that use mobile money to transact with suppliers are more likely to invest. Mobile money also seems to facilitate greater provision of customer credit and generally greater demand for more credit by women-owned firms. Such patterns are not observed for men-owned firms.